Development of a Programmable Logic Controller Based Control System for a Water Plant - M. Abdelrahman, Ali; O.Ali, Magdi; J. Alzubaidi, Abdalrasol (Gezira Journal of Engineering and Applied Sciences, 2021)
The primary objective of this study is to use programmable logic techniques to control the operation of water sucking pumps to supply Bait Elmal plant from the S stream. Basically the proposed system works as follows: the raw water sucking pumps controlled by level sensors inside the water reservoir. The sand filter washing process is automatically initiated by level sensors installed inside the filter basin. Some are used to measure water flow rate and turbidity for adjusting the addition of chemicals    Practically the reservoir has been controlled by using two sensors connected to the raw water pumps through a Programmable Logic Controller (PLC). The filter washing  process valves are open and closed automatically by a signal coming from a control unit. The readings of flow rate, pH, and turbidity devices are used as inputs to the PLC with the aid of a program designed for automatically adjusting the addition of chemical materials      Finally, a complete control system has been successfully tested, where the sucking pumps are installed to supply Bait Elmal water plant from the river Nile. The result obtained prove the reliability and applicability or the system with more advantages at Bait Elmal plant or any similar drinking water plant.